Early and late-onset nonconvulsive status epilepticus after stroke - Göksu, Eylem Özaydın; Genç, Fatma; Atiş, Nesrin; Gömceli, Yasemin Bıçer (Arquivos de Neuro-Psiquiatria, 2021)
Background: Nonconvulsive status epilepticus (NCSE) is a condition that needs timely diagnosis and treatment. It has insignificant clinical features and presents high risk of misdiagnosis. Objective: To investigate NCSE among patients with stroke, given that stroke plays an important role in the etiology of NCSE. Methods: In this retrospective study, acute stroke patients who were admitted and followed up at a stroke outpatient clinic between January 2013 and March 2016 were included. Patients with previous histories of epilepsy, brain tumor, head trauma, hypertensive encephalopathy, arteriovenous malformation, subarachnoid hemorrhage or cerebral venous thrombosis were excluded. Demographic properties, stroke etiology, imaging method, EEG findings, stroke severity according to the NIHSS score, functional disability and modified Rankin Scale were recorded for all patients. Results: Thirty-nine out of 792 stoke patients experienced NCSE. The mean age of the study population was 70±1.2 years (min-max: 46‒90). The study population was composed of 28 females (71.8%) and 11 males (28.2%). NCSE had early onset in 23 patients (59%) and late onset in 16 (41%). The early-onset NCSE patients were older and this was statistically significant between the groups (early onset: 73.5±11.5; late onset: 65.9±12.1; p=0.04). A history of previous stroke was more frequent in the late-onset NCSE group (14; 87,5%) than in the early-onset group (11; 47.8%) (p=0.01). The prognosis was worse in the early-onset group, but without statistical significance. Conclusion: Changes in mental status in the early stages of stroke are mostly attributed to stroke itself, but NCSE should be suspected in the right clinical setting, such as in older patients with suspicious anatomical and clinical associations.
Keywords: Stroke; Epilepsy; Status Epilepticus